5.1. Components of preparedness of future specialists in physical education to professional activity in fitness center - Khrystova, T.; Rebar, I; Abdullaev, Altai; Абдуллаєв, Алтай Карам-Огли; Абдуллаев, Алтай Карам-Оглы (My University, 2020)
The processes of globalization, integration and informatization of society, socio-economic changes in Ukraine have outlined new priorities in the training of specialists in various fields.
Keywords: globalization; informatization of society; specialists; physical education; fitness center